2016
DOI: 10.1155/2016/3856518
|View full text |Cite
|
Sign up to set email alerts
|

Becker’s Nevus Syndrome in a Pediatric Female Patient

Abstract: Becker's nevus syndrome is part of the epidermal nevus syndromes and has been described with a phenotype that includes Becker's nevus, ipsilateral breast hypoplasia, and variable skeletal malformations. It is more frequent in males than in females (5 : 1) but is more relevant in females. The diagnosis is clinically based and the skin lesion must be present and no other numbered criteria have been established, but with more criteria being present the possibility of the diagnosis is higher. Regarding the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The diagnosis is also supported by histology finding of high levels of androgen receptors in the hypoplastic muscles comparable to the levels expressed at the genitals. Biopsy of the skin lesion revealed an increase in the number of smooth muscle bundles, hair follicles, and enlarged papillary crests with pigmentation in basal epidermis [6] .…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is also supported by histology finding of high levels of androgen receptors in the hypoplastic muscles comparable to the levels expressed at the genitals. Biopsy of the skin lesion revealed an increase in the number of smooth muscle bundles, hair follicles, and enlarged papillary crests with pigmentation in basal epidermis [6] .…”
Section: Discussionmentioning
confidence: 99%
“…This syndrome has been thought to be a hormone-dependent disorder because the overexpression of androgen receptors in the Becker's nevus area has been detected [8]. Since androgens also affect hair, muscle, and bone development, this syndrome may be related to the pathogenesis of other systemic manifestations [14].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the relationship between Becker's nevus and other developmental anomalies [11,12]. In 1997, Happle and Koopman suggested a new term of "Becker's nevus syndrome" for the simultaneous presence of a Becker's nevus and other cutaneous, muscular, or skeletal defects, such as hypoplasia of the breast or scoliosis [13,14]. Most of these anomalies tend to coincide with the nevus sites and are mostly ipsilateral [15].…”
Section: Introductionmentioning
confidence: 99%
“…Pigmented patches on exposed areas cause cosmetic concerns, thus warranting medical intervention. Several therapeutic options, including cryotherapy, dermabrasion, surgical excision, oral antiandrogens, and topical glycolic acid, have been proposed [3][4][5]. Laser therapy for BN has recently become increasingly popular.…”
Section: Introductionmentioning
confidence: 99%